LncRNA SNHG8 Promotes Proliferation and Inhibits Apoptosis of Diffuse Large B-Cell Lymphoma via Sponging miR-335-5p - Yu, Bing; Wang, Bo; Wu, Zhuman; Wu, Chengnian; Ling, Juan; Gao, Xiaoyan; Zeng, Huilan (Frontiers in Oncology, 2021)
Long-chain non-coding RNAs (LncRNAs) are expressed in diffuse large B-cell lymphoma (DLBCL) tissues and have played a regulatory role in DLBCL with a cancer-promoting effect. In this study, the role of LncRNA SNHG8 in the regulation of DLBCL cells is investigated, and its underlying mechanism is explored. The database of the Gene Expression Profiling Interactive Analysis (GEPIA) was searched, and the expression of SNHG8 in DLBCL and normal tissues was examined. The expression of SNHG8 was evaluated in several DLBCL cell lines and a normal lymphocyte cell line. It was found that SNHG8 was overexpressed in DLBCL tissues and cells in comparison with their normal counterparts. The short hairpin RNA (shRNA) plasmids of SNHG8 were transfected into DLBCL cells to knockdown the expression of SNHG8, followed by assays of proliferation, colony formation, apoptosis, and related protein expression. The results showed that the knockdown of SNHG8 significantly inhibited DLBCL cell proliferation and colony formation while promoting cell apoptosis. Moreover, the knockdown of SNHG8 reduced the expression of Ki-67, proliferating cell nuclear antigen (PCNA), and Bcl-2 and enhanced the expression of Bax and cleaved caspase 3/9. MiR-335-5p was predicted to be a potential target of SNHG8 by using the bioinformatics analysis, and the interaction between the two was validated by using the dual luciferase assay. In addition, the knockdown of SNHG8 increased the level of miR-335-5p, whereas miR-335-5p mimic decreased the expression of SNHG8. Finally, U2932 cells were co-transfected with or without sh-SNHG8 and miR-335-5p inhibitors, whose proliferation, colony formation, and apoptosis were determined subsequently. It was demonstrated that the presence of an miR-335-5p inhibitor partially canceled the inhibitory effects of the knockdown of SNHG8 on DLBCL cell proliferation and colony formation and the stimulating effects of the knockdown of SNHG8 on cell apoptosis. Taken together, our study suggests that lncRNA SNHG8 exerts a cancer-promoting effect on DLBCL via targeting miR-335-5p.